Flexural strength and surface hardness of nanocomposite denture base resins - Anagha Waghmare; Chandana Nair; Anuj K. Shukla; Mudita Chaturvedi; Tushar Vitthalrao Bhagat; Ebrahim Fihaid Alsubaiy; Ghazala Suleman; Mohasin Abdul Khader; Saurabh Chaturvedi (Heliyon)
Purpose: Higher bending forces during chewing and occlusal loading can lead to the deformation of denture bases. Roughness and microbial adhesion can be the result of improper care of the denture. Many attempts have been made to improve the properties of denture bases through the addition of different materials. The present study aimed to evaluate the surface hardness and flexural strength (FS) of newly formulated nanocomposite denture base resin made by adding zinc oxide (ZnO) and titanium dioxide (TiO2) nanoparticles in heat polymerized polymethyl methacrylate resin in concentrations of 1 % and 2 %. Methods: Rectangular metal master dies of dimension 65mm × 10mm × 3.3 mm for flexural strength and 30mm × 10mm × 3 mm for surface hardness were made. These dies were duplicated in 120 acrylic resin samples. These samples were divided into five groups in which group I is control group samples in conventional resin and group II,III, IV &V contained 1 % and 2 % concentrations of ZnO & TiO2 nanoparticles in heat cure acrylic resin. The processing and finishing of the models were done. Flexural strength was measured using a universal testing machine and surface hardness using a Rockwell hardness testing machine. Results: The minimum SH reported was 101.7 HRM while FS was 81.1 MPa and maximum was 118.7 HRM and 131.8 MPa respectively. The results showed that group IV containing 1 % TiO2 nanoparticles showed the highest surface hardness values whereas the flexural strength was highest in group II containing 1 % ZnO nanoparticles. The analysis of variance showed a p value of <0.001 which was statistically highly significant. Conclusion: Nanocomposite denture base resins modified with ZnO & TiO2 nanoparticles have more flexural strength and surface hardness than conventional denture base resin. Clinical implication: The hardness of a denture base material can be increased by adding these nanoparticles for long term use in oral cavity and in cases prone to denture fracture.